2001
DOI: 10.1164/ajrccm.163.4.2003020
|View full text |Cite
|
Sign up to set email alerts
|

Liver–Lung Interactions Following Escherichia coliBacteremic Sepsis and Secondary Hepatic Ischemia/Reperfusion Injury

Abstract: We hypothesized that ischemia/reperfusion (I/R) injury of the liver during normotensive gram-negative bacteremic sepsis alters the kinetics of circulating endotoxin, tumor necrosis factor-alpha (TNF-alpha), and coinduced mediators, thereby exacerbating sepsis-induced lung inflammation. Liver and lung dysfunction were studied after hematogenous infection of Sprague-Dawley rats with 10(9) Escherichia coli serotype O55:B5 (EC) and 90 min of secondary hepatic ischemia in EC + I/R and saline-infused (normal saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 27 publications
0
26
0
2
Order By: Relevance
“…Colletti et al (8,9) showed intra-alveolar PMN infiltration 12 h after reperfusion that followed 90 min of lobar hepatic ischemia. In contrast, Matuschak et al (22) showed a lung PMN influx 1 h after reperfusion that was not present 24 h after reperfusion. The reason for such diverse results is thought to be due to variations in the experimental design, including differences in: the duration of ischemia; the type of hepatic inflow obstruction (total or partial); respiration during the reperfusion period; the timing of the examinations after reperfusion; and the animal species that were studied.…”
Section: Discussionmentioning
confidence: 87%
“…Colletti et al (8,9) showed intra-alveolar PMN infiltration 12 h after reperfusion that followed 90 min of lobar hepatic ischemia. In contrast, Matuschak et al (22) showed a lung PMN influx 1 h after reperfusion that was not present 24 h after reperfusion. The reason for such diverse results is thought to be due to variations in the experimental design, including differences in: the duration of ischemia; the type of hepatic inflow obstruction (total or partial); respiration during the reperfusion period; the timing of the examinations after reperfusion; and the animal species that were studied.…”
Section: Discussionmentioning
confidence: 87%
“…In the I/R group, animals were anesthetized with pentobarbital 50 mg/kg intraperitoneally. An external jugular vein catheter was created using a polyethylene tube of 0.9 mm inner diameter (Becton Dickinson Medical Devices, Suzhou, China) and the rats were subjected to midline lapSodium Nitroprusside Regulates LTC4 Synthesis Enzyme mRNA Expressions Pharmacology 2007;80: [11][12][13][14][15][16][17][18][19][20] 13 arotomy. The liver was exposed, and the left lateral and median lobes were rendered ischemic by clamping the hepatic arterial and portal venous blood supply using a microaneurysm clamp.…”
Section: Animal Model Of Hepatic I/r Injurymentioning
confidence: 99%
“…In the same vein, IL-6 is a pleotropic cytokine which was initially recognized for its regulation of acute protein synthesis and the acute inflammatory response [22,23]. Recently, IL-6 has been reported to be upregulated in several animal models of hepatic injury [24][25][26], and its mRNA expression was enhanced in the liver of wild-type mice injected with APAP [19]. Interestingly, these pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, could be blocked from release from hepatic cells treated with NAM [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%